Implementation of Independent Curriculum Learning in Islamic Education and Character Subjects at MIN 1 Palembang - Ahmad Zainuri (Edukasi Islami : Jurnal Pendidikan Islam, 2022)
This article is entitled the Implementation of Independent Curriculum Learning in Islamic Education and Character Subjects at MIN 1 Palembang. This type of research is qualitative, with the types and sources of data, namely primary and secondary data. Data collection techniques used in this study were through interviews, observation and documentation. Meanwhile, the researcher's data analysis technique consisted of data reduction, data presentation, verification and checking the validity of the data. After the data is collected, the next step is to analyze the data, with stages, namely data collection, data reduction, data display and conclusion drawing/verification. The results show that the implementation of the independent curriculum learning leads to Pancasila students which aims to realize Indonesian students as lifelong students who have global competence and behave in accordance with Pancasila values, with six main characteristics, namely faith, fear of God Almighty, and noble character. This is carried out well in madrasas because monotheism and moral education are the foundation for schools. Global diversity means that students in madrasas are educated to recognize and understand the context between nations so that a sense of tolerance and togetherness arises. Mutual cooperation in madrasas is accustomed to group work so that cooperation and mutual assistance is built, and it is also accustomed to caring for others. Independent attitude is independence taught in madrasas, which aims to make students have strong personalities, do not depend on others, and think critically. For madrasas, the attitude of critical reasoning aims to make students active, and have strong thinking power so that students become creative.